A multiwavelength study of the debris disc around 49 Cet. Issue 3 (17th July 2019) - Pawellek, Nicole; Moór, Attila; Milli, Julien; Kóspál, Ágnes; Olofsson, Johan; Ábrahám, Péter; Keppler, Miriam; Kral, Quentin; Pohl, Adriana; Augereau, Jean-Charles; Boccaletti, Anthony; Chauvin, Gaël; et al.
Abstract: In a multiwavelength study of thermal emission and scattered light images we analyse the dust properties and structure of the debris disc around the A1-type main-sequence star 49 Cet. As a basis for this study, we present new scattered light images of the debris disc known to possess a high amount of both dust and gas. The outer region of the disc is revealed in former coronagraphic H -band and our new Y -band images from the Very Large Telescope SPHERE instrument. We use the knowledge of the disc's radial extent inferred from ALMA observations and the grain size distribution found by spectral energy distribution fitting to generate semidynamical dust models of the disc. We compare the models to scattered light and thermal emission data and find that a disc with a maximum surface density at 110 au and shallow edges can describe both the thermal emission and the scattered light observations. This suggests that grains close to the blow-out limit and large grains stem from the same planetesimal population and are mainly influenced by radiation pressure. The influence of inward transport processes could not be analysed in this study.